2007
DOI: 10.1007/s10453-007-9073-z
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Aerobiology Modeling System applied to the spread of soybean rust into the Ohio River valley during September 2006

Abstract: Soybean rust (Phakopsora pachyrhizi) has recently invaded North America and has the potential to be the most destructive foliar disease of soybean. As part of the response to this threat, the Integrated Aerobiology Modeling System (IAMS) was constructed to forecast the aerial movement of this pathogen from subtropical to middle latitude portions of the continent. IAMS simulations have been conducted daily for the past two growing seasons and integrated with information from a nationwide observation network int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 22 publications
0
29
0
2
Order By: Relevance
“…Rapidly evolving computational resources provide platforms for integrating large-extent data into disease risk mapping. National-level analysis of soybean rust in the United States is a striking example of data integration in near real-time in support of decision making for management (60,61).…”
Section: Mining Complex Epidemiological Data: Prospects and Challengesmentioning
confidence: 99%
“…Rapidly evolving computational resources provide platforms for integrating large-extent data into disease risk mapping. National-level analysis of soybean rust in the United States is a striking example of data integration in near real-time in support of decision making for management (60,61).…”
Section: Mining Complex Epidemiological Data: Prospects and Challengesmentioning
confidence: 99%
“…Vegetation in agricultural areas is therefore a likely main source of Alternaria spores in many parts of Europe. Studies from the USA have shown that spores from agricultural areas that are infected with soybean rust (P. meibomiae and P. pachyrhizi) have the potential to be transported more than 1000 km under favourable weather conditions (Isard et al, 2005(Isard et al, , 2007. European studies on other aeroallergens have shown that the overall load in a region is typically due to local sources with intermittent long distance transport from remote regions Smith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the continental United States, SBR forecasts are generated using complex simulation models that integrate biological, geographical and weather data to simulate spatial and temporal soybean rust progress arising from known inoculum sources early during the season (Isard et al 2007). Other efforts in disease risk outlooks include the use of rainfall forecasts from regional climate models for the following 30 or 15 days (combined with observed 15 days) to generate maps outlining areas in the country favorable for epidemic development (Del Ponte and Yang 2006).…”
Section: Discussionmentioning
confidence: 99%